Fetoscopy and laser photocoagulation in the treatment of twin-to-twin transfusion syndrome: series of cases treated in Peru - Ventura Laveriano, Walter (2019)
Twin-to-twin transfusion syndrome is a severe complication of twin monochorial pregnancies manifested with one hypovolemic fetus (donor) and another hypervolemic fetus (receiver). Perinatal mortality is about 90 to 100% if untreated. The accepted treatment is fetoscopy and selective laser photocoagulation of the placental shunts that connect both twins. Currently, this specialized procedure is only performed in our institution. We present the first cases of monochorionic twin pregnancy complicated with twin-to-twin transfusion syndrome that underwent laser photocoagulation and fetoscopy.